PENGARUH KEBIJAKAN PENDANAAN, INSIDER OWNERSHIP DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2013 - Supriyanah Supriyanah (Jurnal Riset Bisnis Indonesia, 2015)
This research is conducted for testing the influence of debt to equity ratio, insider ownership andfirm size to price book value with the dividend payout ratio as the intervening variable in the firmsregistered at Indonesian Capital Market in the period of 2010 through 2013. Sampling techniqueapplied in this research is purposive sampling. The data are collected based on the publication ofIndonesian Capital Market Directory and www.idx.co.id. A number of 36 sample companies out of 472companies registered at Indonesian Capital Market are obtained. Analytic technique applied in thisresearch is double linier regression to obtain a thorough picture of the relation between one variableand the others. This research is measured by seeing the determination coefficient, statistic value of F,statistic value of t, and intervening test. Besides, classic assumption test is also conducted, involvingnormality, multicollinearity, auto-correlation, and heteroscedasticity tests. The analysis result showsthat DER variable partially influences significantly negative to DPR, insider ownership variablepartially influences significantly positive to DPR, firm size variable partially influences significantlypositive to DPR, DER variable partially influences significantly negative to PBV, insider ownershipvariable influences significantly positive to PBV, firm size variable partially influences significantlypositive to PBV and DPR variable partially influences significantly positive to PBV. The regressiontest result with intervening variable states that Dividend Policy (DPR) is not intervening variable, Debtto Equity Ratio (DER) variable, insider ownership and firm size toward Price Book Value (PBV).Keywords: Debt to Equity Ratio, insider ownership, firm size, dividend payout ratio and price bookvalue